Hormônios tireoideanos, qualidade de carcaça e de carne e desempenho produtivo de suínos em crescimento e terminação - Storti, Andressa Alves (2011)
The objective of this study was to compare serum concentrations of the hormones triiodothyronine (T3) and thyroxine (T4) in pigs on commercial line beginning and end of growing-finishing phase, correlating them with productive performance, carcass and meat quality. Blood samples were collected from 48 animals at the beginning and end of growing-finishing phase by puncturing the jugular vein, around the same time (08:00 to 10:00). Measurements of serum thyroid hormones were made by enzyme-immunoassay for the quantitative determination of serum concentrations of T3 and T4 in pigs, multichannel analyzer in automatic Chemewell®, using the kit Interkit (Bio check, Inc.). The temperature and relative humidity were measured during the experimental period and the black globe humidity index (BGHI) was calculated to characterize the environment. The following characteristics of productive performance, carcass quality and meat were measured: Initial body weight (IBW), final body weight (FBW), average body weight gain (BWG), backfat thickness at first rib (BTFR), backfat thickness at last rib (BTLR), backfat thickness at the last lumbar (BTLL), carcass length (CL), length of small intestine (SI), lean meat percentage (LM%), pH at 45 minutes (pH45min), pH at 24 hours (pH24h), temperature at 1 minute (T1min), temperature at 24 hours (T24h). The values of temperature, BGHI and relative humidity were hight, characterizing the stressful environment. The T4 and T3 values decreased with increasing age of pigs. It was verified that final T3 negatively and moderately correlated with FBW and BWG, as final T4 with IBW (p<0.05). Initial and final thyroxine negatively and moderately correlated with pH45min and pH24h, respectively (p<0.05). The FBW positively and moderately correlated with BTFR, BTLR, BTLL, CL, SL, but negatively and moderately with LM% (p<0.05). Thus, values of T3 and T4 in pigs early in the growing-finishing phase are larger than in termination. These hormones influence the initial and final weight, BTLL, pH45min and pH24h of growing-finishing pigs.